Realization of the right to adequate food and the nutritional status of land evictees: a case for mothers/caregivers and their children in rural Central Uganda - Aziiza Nahalomo; Per Ole Iversen; Peter Milton Rukundo; Archileo Kaaya; Joyce Kikafunda; Wenche Barth Eide; Maritha Marais; Edward Wamala; Margaret Kabahenda (BMC, 2018)
Abstract Background In developing countries like Uganda, the human right to adequate food (RtAF) is inextricably linked to access to land for households to feed themselves directly through production or means for its procurement. Whether RtAF is enjoyed among Ugandan land evictees, is unknown. We therefore explored this among land evictees (rights-holders) in Wakiso and Mpigi districts in rural Central Uganda. We assessed food accessibility and related coping strategies, diet quality and nutritional status of children 6-59 months old, and their caregivers. Effectiveness of the complaint and redress mechanisms in addressing RtAF violations was also explored. Methods In this cross-sectional study, quantitative data was collected using a structured questionnaire, with food security and nutritional assessment methods from a total of 215 land evictees including 187 children aged 6-59 months. Qualitative data was collected by reviewing selected national and international documents on the RtAF and key informant interviews with 15 purposively sampled duty-bearers. These included individuals or representatives of the Uganda Human Rights Commission, Resident District Commissioner, Sub-county Chiefs, and local Council leaders. Results We found that 78% of land evictees had insufficient access to food while 69.4% had consumed a less diversified diet. A majority of evictees (85.2%) relied on borrowing food or help from others to cope with food shortages. Of the 187 children assessed, 9.6% were wasted, 18.2% were underweight and 34.2% were stunted. Small, but significant associations, were found between food accessibility, diet quality, food insecurity coping strategies; and the nutritional status of evictees. We observed that administrative, quasi-judicial and judicial mechanisms to provide adequate legal remedies regarding violations of the RtAF among evictees in Uganda are in place, but not effective in doing so. Conclusion Land eviction without adequate legal remedies is a contributor to food insecurity and undernutrition in rural Central Uganda. It is essential that the Government strengthens and enforces the policy and legal environment to ensure adequate and timely compensation of evictees in order to reduce their vulnerability to food insecurity.